Unpacking the enablers and barriers to digital transformation in Vietnamese logistics companies: A qualitative analysis - Vu, Phong Trong; Nguyen, H. X.; Pham, Quynh T. T.; Nguyen, P. V. (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores the enablers and barriers to digital transformation in Vietnamese logistics companies, a sector pivotal to the nation’s economic growth yet lagging in digital adoption. The core theme centers on understanding how local contextual factors shape the integration of technologies like artificial intelligence, IoT, and blockchain in an emerging market. The research objectives are to identify key facilitators of digital transformation, examine obstacles impeding progress, and offer strategic recommendations for logistics firms to enhance their digital maturity. Data were collected through semi-structured interviews with 20 stakeholders, logistics managers, policymakers, and technology providers, representing firms of varying sizes and digital maturity levels, supplemented by secondary sources such as industry reports and government policies. A qualitative, exploratory approach was employed, with thematic analysis conducted using NVivo software to identify recurring patterns. Findings reveal that leadership vision, government incentives, affordable technological ecosystems, and workforce training are primary enablers, fostering organizational and technical capacity for digital adoption. Conversely, financial constraints, cultural resistance, regulatory complexities, and cybersecurity risks emerge as significant barriers, particularly pronounced due to the prevalence of small and medium enterprises and traditional practices. These insights highlight Vietnam-specific nuances, such as the reliance on cost-effective solutions and the critical role of upskilling, distinguishing this study from global trends. The research contributes to logistics scholarship by offering a localized perspective and provides practical strategies for firms and policymakers to navigate digital transformation challenges effectively.